The Implementation of Intercultural Communicative Competence in Evaluation: An Analysis of English Summative Assessment - Dinar Martia Azizah; Aditya Sahrul Akbar (FKIP UNIVERSITAS PAKUAN, 2025)
Assessment plays an important role in supporting an effective and responsible learning process. Thus, this study aims to analyze the implementation of the Intercultural Communicative Competence (ICC) component in the summative assessment of English in one of the vocational high schools in Yogyakarta. The qualitative approach with thematic content analysis method were implemented in this research and the data were collected from 30 students of odd semester summative exam questions and analyzed using the theoretical framework which includes of three main components: knowledge, skills, and attitudes. The results showed that six questions contained ICC elements, namely one question reflected the knowledge component and five questions reflected the skills component. No questions were found that represented the attitude component. This finding indicates that although there have been efforts to integrate ICC in assessment, its implementation is still limited and has not been applied systematically. The dominance of the skills component indicates a focus on the ability to interpret and understand cross-culturally, but the absence of the attitude aspect indicates that intercultural sensitivity has not been adequately measured. Futhermore, it can be concluded that the application of ICC in summative assessment is still partial and emphasizes the cognitive aspect. This study emphasizes the need to develop more comprehensive assessment instruments that cover all ICC components to support students' intercultural awareness in accordance with the objectives of the Merdeka Curriculum.